Pancreas divisum: Analysis and therapeutic alternatives with a case report - Jokić Radoica; Milošević Pavle; Konstantinidis Georgios; Vlaški Jovan; Beserminji Miroslav (Vojnosanitetski Pregled)
Introduction. Pancreas divisum is a relatively common pancreatic duct anatomic variant, firstly described in the 17th century. Case report. We reported a 2-year-old child admitted to the Pediatric Clinic with breathing difficulties and abdominal pains. Examination and X-ray image, showed a vast right hydrothorax containing rusty coloured solution with a high degree of amylase. Ultrasound and computed tomography examination revealed pancreatic polycyclic pseudocysts; following magnetic resonance cholangiopancreatography (MRCP), the diagnosis of pancreas divisum was confirmed. The general condition of the patient worsened, requiring an urgent operation. External drainage of the perforated pancreatic pseudocyst was performed. Following external fistula maturation, a change from external to internal drainage was performed using Roux-en-Y fistulojejunostomy. A 3-year postoperative period was uneventful. Conclusion. Pancreas divisum cases are unique requiring clinical experience, rational approach, and complex multimodal management. MRCP is a valuable diagnostic method. Amongst therapeutic options, outer and internal drainage can be seen as reliable methods. Further investigations are absolutely required to determine practical and appropriate conclusions.